2012
DOI: 10.1098/rspb.2012.0963
|View full text |Cite
|
Sign up to set email alerts
|

Natural simian immunodeficiency virus transmission in mandrills: a family affair?

Abstract: Understanding how pathogens spread and persist in the ecosystem is critical for deciphering the epidemiology of diseases of significance for global health and the fundamental mechanisms involved in the evolution of virulence and host resistance. Combining long-term behavioural and epidemiological data collected in a naturally infected mandrill population and a Bayesian framework, the present study investigated unknown aspects of the eco-epidemiology of simian immunodeficiency virus (SIV), the recent ancestor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Only 6.8% (11/161) of the sooty mangabey infants from the Yerkes National Primate Research Center were reported to have acquired SIV by presumptive MTIT, based on the presence of anti-SIV antibodies without seroreversion and a viral load of >500 copies/ml of serum in the first year of life [25]. This study corroborates the data obtained in the wild AGMs and expands upon previous studies performed in captive NHPs [4,14,18,20,21,24]. Importantly, the viral loads of the 11 infants presumed to be infected by MTIT were 1-2 log lower than that of sooty mangabeys infected as adults, suggesting not only a block to SIV transmission, but also restriction of SIV replication in infant natural hosts [25].…”
Section: Studies In Captive Monkeys From Primate Centerssupporting
confidence: 93%
See 2 more Smart Citations
“…Only 6.8% (11/161) of the sooty mangabey infants from the Yerkes National Primate Research Center were reported to have acquired SIV by presumptive MTIT, based on the presence of anti-SIV antibodies without seroreversion and a viral load of >500 copies/ml of serum in the first year of life [25]. This study corroborates the data obtained in the wild AGMs and expands upon previous studies performed in captive NHPs [4,14,18,20,21,24]. Importantly, the viral loads of the 11 infants presumed to be infected by MTIT were 1-2 log lower than that of sooty mangabeys infected as adults, suggesting not only a block to SIV transmission, but also restriction of SIV replication in infant natural hosts [25].…”
Section: Studies In Captive Monkeys From Primate Centerssupporting
confidence: 93%
“…Surveys performed in the Primate Centers with large colonies of naturally infected natural hosts also reported a very low rate of vertical transmission in these species [6,14,18,24,25]. Only 6.8% (11/161) of the sooty mangabey infants from the Yerkes National Primate Research Center were reported to have acquired SIV by presumptive MTIT, based on the presence of anti-SIV antibodies without seroreversion and a viral load of >500 copies/ml of serum in the first year of life [25].…”
Section: Studies In Captive Monkeys From Primate Centersmentioning
confidence: 90%
See 1 more Smart Citation
“…They also focus on mechanisms occurring at the withinhost level (e.g., mediated by the host immune system, Table 1), whereas, as will be developed further, interactions between parasites can also occur via mechanisms occurring at the host population [26] and probably higher levels of organization. Interaction mechanisms resulting in particular from host behavior have been largely ignored, despite its crucial role in transmission processes [27]. A mechanistic approach, aiming at deciphering the underlying processes of parasite-parasite interactions, is necessary to go beyond the simple description of parasite associations patterns.…”
Section: Parasite-parasite Interactions: From the Lab To The Fieldmentioning
confidence: 99%
“…Because they are extremely difficult to observe and follow in their densely forested wild habitat (Abernethy et al, 2002;Bret et al, 2013), like many NHPs, especially monkeys, mandrills are also poorly studied. The colony of mandrills housed at the International Centre for Medical Research in Franceville (CIRMF), Gabon, offers a unique opportunity to unravel a number of unexplored aspects of host-microbe interactions in NHPs in general, and in mandrills in particular (Fouchet et al, 2012;Bret et al, 2013;Roussel et al, 2015). This population lives in semi-captive conditions offering the possibility to monitor individuals throughout their lives while preserving a wild population dynamic.…”
Section: Introductionmentioning
confidence: 99%